2016
DOI: 10.1016/j.drugalcdep.2016.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone without the needle − systematic review of candidate routes for non-injectable naloxone for opioid overdose reversal

Abstract: . (2016). Naloxone without the needle systematic review of candidate routes for non-injectable naloxone for opioid overdose reversal. Drug and Alcohol Dependence. DOI: 10.1016DOI: 10. /j.drugalcdep.2016 Citing this paper Please note that where the full-text provided on King's Research Portal is the Author Accepted Manuscript or Post-Print version this may differ from the final Published version. If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
(39 reference statements)
2
36
0
1
Order By: Relevance
“…To supplement and cross‐check the data obtained in Stages 1 and 2, we also searched PubMed for human PK data for non‐injectable naloxone using the Boolean search query ‘(nasal OR intranasal OR nose OR buccal OR sublingual) AND naloxone AND pharmacokinetics’ (see Table S1 for search protocol). These three routes of administration were chosen based on the systematic review .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To supplement and cross‐check the data obtained in Stages 1 and 2, we also searched PubMed for human PK data for non‐injectable naloxone using the Boolean search query ‘(nasal OR intranasal OR nose OR buccal OR sublingual) AND naloxone AND pharmacokinetics’ (see Table S1 for search protocol). These three routes of administration were chosen based on the systematic review .…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review applied the FDA criteria to the peer‐reviewed literature and identified three candidate routes of administration for injection‐free naloxone delivery: IN, sublingual and buccal. However, at the time of the FDA approval of the first nasal spray, no results from clinical trials on the new nasal spray were published, and human PK data were only reported in one peer‐reviewed publication for an improvised IN naloxone spray formulation (2 mg 5 mL −1 ), with extremely low bioavailability (F = 4%) .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review identified nasal, buccal and sublingual naloxone delivery as the three viable routes for naloxone administration in an overdose emergency, of which study of the nasal route was most advanced (Strang et al, 2016a).…”
Section: Non-injectable Naloxonementioning
confidence: 99%
“…point to a potential nose‐to‐brain direct absorption and suggest that ‘blood bioavailability and pharmacokinetics may be the wrong yardstick by which to model nasal drug effects’. We have considered this briefly elsewhere where we have noted that Ehrick et al . do not consider it as a significant route of nasal absorption in man , and that Djupesland et al .…”
Section: Agreementmentioning
confidence: 99%
“…We have indeed sought to encourage the pharmaceutical industry to become involved in developing and delivering new forms of naloxone which would be better suited to this new application (mainly with very little success)—this includes better forms of injectable naloxone [e.g. pre‐filled syringes of naloxone (preferably with stake needle), more portable formulations of naloxone, better demonstrated and authorized shelf‐life], possible new non‐injectable naloxone formulations, such as concentrated nasal naloxone spray , and also potentially buccal naloxone (see for a recent review). We believe this collaboration is important, and we wish we had been able to be more influential and to stimulate earlier better developments.…”
Section: Agreementmentioning
confidence: 99%